Central nervous system infections in patients with systemic lupus erythematosus: a systematic review and meta-analysis - Kasra Molooghi; Fereshte Sheybani; Hamidreza Naderi; Zahra Mirfeizi; Negar Morovatdar; Ashkan Baradaran (Lupus Science and Medicine, 2022)
We aimed to conduct a systematic review and meta-analysis of studies on central nervous system (CNS) infections in patients with SLE, in order to describe their clinical and microbiological characteristics, and outcomes. A systematic search of PubMed/Medline and Embase electronic databases was performed (March 2021) to identify all published studies on CNS infections and their characteristics in patients with SLE. A random-effects model was adopted and findings were reported with 95% CI. Overall, 6 studies involving 17 751 patients with SLE and 209 SLE cases with CNS infection were included in our meta-analysis. The frequency rate of CNS infections in patients with SLE was 0.012 (95% CI: 0.008 to 0.018). Meningitis was the most common clinical syndrome (93.5%, n=109/114, 95% CI: 82.6% to 97.8%) and Cryptococcus neoformans (35.9%, n=55, 95% CI: 27.2% to 45.7%) and Mycobacterium tuberculosis (27.1%, n=43, 95% CI: 14.6% to 44.8%) were the most common causative pathogens. Our patient-pool showed a mean SLE Disease Activity Index (SLEDAI) score of 7.9 (95% CI: 6.1 to 9.6), while 92.4% (n=72/76, 95% CI: 83.0% to 96.8%) of cases were on oral systemic corticosteroids, with a prednisone equivalent mean daily dose of 30.9 mg/day (95% CI: 18.0 to 43.7). Our meta-analysis revealed a mortality rate of 29.0% (95% CI: 15.0% to 48.6%). Clinicians should maintain a high index of suspicion for cryptococcal and tuberculosis (TB) meningitis in patients with SLE with suspected CNS infection, particularly in those with higher SLEDAI and on higher doses of systemic corticosteroids. In conclusion, initiation of empiric antituberculous treatment for patients with SLE who are highly suspected to have CNS TB is warranted while awaiting the results of diagnostic tests. Antifungals might also be potentially useful empirically in patients with SLE who are suspected to have fungal CNS infections. However, with respect to side effects such as toxicity and high cost of antifungals, decision regarding early antifungal therapy should be guided by early and less time-consuming fungal diagnostic tests.